Bone mineral density and microarchitecture in patients with essential thrombocythemia and polycythemia vera. Issue 2 (February 2017) - Farmer, S.; Shanbhogue, V.; Hansen, S.; Stahlberg, C.; Vestergaard, H.; Hermann, A.; Frederiksen, H.
Abstract Summary In this cross-sectional study of 45 patients with myeloproliferative neoplasms, we found no evidence of secondary osteoporosis. Introduction Patients with essential thrombocythemia (ET) and polycythaemia vera (PV) are at increased risk of fractures but the underlying mechanisms have not been settled. We conducted a study to assess bone mineral density, microarchitecture, estimated bone strength and global bone turnover in 45 patients with ET or PV. Methods Patients were evaluated in a cross-sectional study with dual energy X-ray absorptiometry (DXA) at the hip and spine; high-resolution peripheral quantitative computed tomography (HR-pQCT) at the distal radius and distal tibia; and biochemical markers of bone turnover including pro-collagen type 1 N-terminal pro-peptide, osteocalcin, C-terminal cross-linking telopeptide of type 1 collagen and bone-specific alkaline phosphatase. Also, 45 healthy comparisons, matched on age, height and weight with each patient were included as control subjects. Results Patients and comparisons had almost identical BMDs: 0.96 (IQR: 0.85–1.07) g/cm2 and 0.96 g/cm2 (IQR: 0.86–1.05 g/cm2 ), respectively. As well all microarchitecture and estimated bone strength measures were highly similar in the two groups. Levels of bone turnover markers were within reference values in patients. Conclusion These results reveal no evidence of secondary osteoporosis among patients with ET or PV. The mechanism behind the increased fracture risk in ET or PV patients remains unknown.